2009
DOI: 10.1186/1471-244x-9-77
|View full text |Cite
|
Sign up to set email alerts
|

Association of various reproductive rights, domestic violence and marital rape with depression among Pakistani women

Abstract: BackgroundDepression among women is common in developing countries. Gender inequality can contribute to women's risk for depression. Lack of reproductive and sexual rights is an important marker of gender inequality and women do not have the freedom to express their reproductive and sexual needs in many parts of the world. Therefore we designed this study to determine the association of depression with lack of various reproductive rights and domestic violence among married women in Karachi, Pakistan.MethodsA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 18 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…Slapping and pushing were the most commonly reported forms of physical abuse (Fikree & Bhatti, 1999).The prevalence of physical IPV was reported in 20 studies (Ali et al, 2009;Ali et al, 2005;Ali, Asad et al, 2011;Ali, Mogren et al, 2011;Asif et al, 2010;Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2006;Fikree et al, 2005;Kapadia et al, 2010;Karmaliani et al, 2008;Niaz et al, 2002;Rabbani et al, 2008;Shaikh, 2000Shaikh, , 2003Shaikh et al, 2008;Zareen et al, 2009). The lifetime prevalence of physical IPV, defined as experiencing physical IPV at least once during the marital period, ranged from 16%-80% with the six studies reporting a life time prevalence of physical IPV between 28%-35% Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2004;Niaz et al, 2002;Shaikh, 2000).…”
Section: Physical Ipvmentioning
confidence: 99%
See 3 more Smart Citations
“…Slapping and pushing were the most commonly reported forms of physical abuse (Fikree & Bhatti, 1999).The prevalence of physical IPV was reported in 20 studies (Ali et al, 2009;Ali et al, 2005;Ali, Asad et al, 2011;Ali, Mogren et al, 2011;Asif et al, 2010;Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2006;Fikree et al, 2005;Kapadia et al, 2010;Karmaliani et al, 2008;Niaz et al, 2002;Rabbani et al, 2008;Shaikh, 2000Shaikh, , 2003Shaikh et al, 2008;Zareen et al, 2009). The lifetime prevalence of physical IPV, defined as experiencing physical IPV at least once during the marital period, ranged from 16%-80% with the six studies reporting a life time prevalence of physical IPV between 28%-35% Farid et al, 2008;Fikree & Bhatti, 1999;Fikree et al, 2004;Niaz et al, 2002;Shaikh, 2000).…”
Section: Physical Ipvmentioning
confidence: 99%
“…Shouting, yelling and the use of abusive language were the most frequently reported acts perpetrated by husbands (Fikree et al, 2005). Only nine studies (Ali et al, 2009;Ali et al, 2005;Ali & Bustamante-Gavino, 2007;Fikree & Bhatti, 1999;Fikree et al, 2006;Fikree et al, 2005;Karmaliani et al, 2008;Rabbani et al, 2008;Shaikh, 2000Shaikh, , 2003Zareen et al, 2009) specifically reported verbal abuse, the prevalence of which varied between 31% (Karmaliani et al, 2008) and 100% (Rabbani et al, 2008;Shaikh, 2000). The frequency of verbal IPV was reported to decrease in pregnancy in two studies -Karamaliani et al…”
Section: Psychological Ipvmentioning
confidence: 99%
See 2 more Smart Citations
“…Suicidal thoughts were reported by 65% -74% of women exposed to physical, sexual or psychological violence [23]. Similarly, another study showed that depression in married women in Pakistan was strongly associated with domestic abuse by in-laws (OR 4.91; 95% CI = 2.66, 9.06) and marital rape (OR 3.03; 95% CI = 1.50, 6.11) when compared with a control group [24].…”
Section: Discussionmentioning
confidence: 99%